Insulin-Producing Cell Transplantation Platform for Veterinary Practice - Kuncorojakti, Suryo; Srisuwatanasagul, Sayamon; Kradangnga, Krishaporn; Sawangmake, Chenphop (Frontiers in Veterinary Science, 2020)
Diabetes mellitus (DM) remains a global concern in both human and veterinary medicine. Type I DM requires prolonged and consistent exogenous insulin administration to address hyperglycemia, which can increase the risk of diabetes complications such as retinopathy, nephropathy, neuropathy, and heart disorders. Cell-based therapies have been successful in human medicine using the Edmonton protocol. These therapies help maintain the production of endogenous insulin and stabilize blood glucose levels and may possibly be adapted to veterinary clinical practice. The limited number of cadaveric pancreas donors and the long-term use of immunosuppressive agents are the main obstacles for this protocol. Over the past decade, the development of potential therapies for DM has mainly focused on the generation of effective insulin-producing cells (IPCs) from various sources of stem cells that can be transplanted into the body. Another successful application of stem cells in type I DM therapies is transplanting generated IPCs. Encapsulation can be an alternative strategy to protect IPCs from rejection by the body due to their immunoisolation properties. This review summarizes current concepts of IPCs and encapsulation technology for veterinary clinical application and proposes a potential stem-cell-based platform for veterinary diabetic regenerative therapy.